INTEGRASI NILAI-NILAI KEADILAN DAN ETIKA MUAMALAH DALAM KITAB AL-AMWAL KARYA ABU ‘UBAID TERHADAP PENGEMBANGAN HUKUM EKONOMI SYARIAH DI ERA DIGITAL - Munandar, Muhammad Arief; Muhammad Aulia; Azhary, Kamal (Journal of Sharia Economics, 2026)
Digital economic transformation poses significant challenges to sustaining the values of justice and Islamic muamalah ethics that underpin Sharia economic law. Rapid developments in fintech, e-commerce, and blockchain have not been fully accompanied by the optimal implementation of Sharia principles in digital practices. This study aims to integrate the principles of justice (‘adl) and classical muamalah ethics trustworthiness, honesty (ṣidq), and social responsibility contained in Abu ‘Ubaid’s Kitab al-Amwāl into the development framework of Islamic economic law in the digital era. Using a systematic literature review (SLR) with a library research approach, primary and secondary sources were collected from Scopus, Google Scholar, and DOAJ databases. Out of approximately 200 identified publications, 42 selected articles were analyzed through content analysis and conceptual-historical normative approaches. The findings reveal that justice in al-Amwāl emphasizes fair wealth distribution, a balance between individual ownership and public interest, and the state’s responsibility for ensuring social welfare. These muamalah ethical values remain relevant as a foundation for transparent, accountable, and equitable Sharia-based digital economic governance. The study concludes that Abu ‘Ubaid’s thought provides a strong conceptual basis for developing adaptive, ethical, and maqāṣid-oriented Islamic digital economic law.